Evaluation of Factors Affecting the Competitive Advantage of Organizations in Establishing Sustainable Project Management Post Covid-19 - Abdulrahman S. Bageis; Ahsan Waqar; Nadhim Hamah Sor; Hamad Almujibah; Abdul Hannan Qureshi; P. Jagadesh; Ahmed Farouk Deifalla; Muhammad Basit Khan; Yakubu Dodo; Mohamed Moafak Arbili; Mohammed Awad Abuhussain; Omrane Benjddou (Journal of Engineering)
Competitive advantage significantly matters for modern construction organizations as it promotes the sustainable development and safety management of projects. UK construction organizations have greatly suffered from a lack of safety and sustainability of project management in infrastructure development projects because of the COVID-19 pandemic. Post-COVID-19 UK infrastructure development projects are uncertain in the context of organizational competitive advantage as they cannot maintain sustainable project management. This study was conducted to identify, rank, and present a framework of factors influencing the competitive advantage of UK organizations. The study design involved identifying factors from the current literature, after which the most relevant factors were filtered with the help of semi-structured interviews with 15 experts. A pilot survey was conducted then, involving 192 respondents, after which a reliability test and exploratory factor analysis (EFA) were conducted on the results. A primary questionnaire survey involving 250 respondents was conducted, after which RII and confirmatory factor analysis (CFA) were conducted on the final data. A total of five subgroups were found to be significant in the CFA, such as Resources and Policies, Quality and Delays, Motivation and Expectation, Management and Environment, and Government and Business. It is recommended based on findings that the construction organizations of the UK have to consider working on identified factors to maintain a competitive advantage in establishing sustainable project management solutions for post-COVID-19 UK infrastructure development projects.